PENINGKATAN KECERDASAN KINESTETIK MELALUI TARI KREATIF UNTUK ANAK USIA 5-6 TAHUN DI TAMAN KANAK-KANAK ASSAID LARANGAN - Loveita Meitarani (Universitas Muhammadiyah Jakarta, 2019)
This study aims to determine whether creative dance activities (Sundanese Sundanese) can improve kinesthetic intelligence in children aged 5-6 years in the Assaid Kindergarten Prohibition. Classroom action model (CAR) or classroom action research with research subjects consisting of 14 students, 8 boys and 6 girls. As per the results of the data obtained in the research carried out in the Assaid Kindergarten the prohibition of the percentage of children's kinesthetic intelligence in the Assaid Kindergarten Prohibition before the action is carried out is 35%. The target set by researchers and collaborators is 75%. After the action was implemented, it showed an increase in cycle 1 when compared to the pre cycle, which was 68%. However, because the results obtained are not yet in line with the eating target implemented in the second cycle and the results have increased by 90%. So this research can be declared successful. These results indicate compliance with the action hypothesis that is kinesthetic intelligence of children aged 5-6 years in Assaid Kindergarten Prohibition can be increased through creative dance (Sundanese Sundanese).